2019
DOI: 10.3390/rs11101151
|View full text |Cite
|
Sign up to set email alerts
|

SenDiT: The Sentinel-2 Displacement Toolbox with Application to Glacier Surface Velocities

Abstract: Satellite imagery represents a unique opportunity to quantify the spatial and temporal changes of glaciers world-wide. Glacier velocity has been measured from repeat satellite scenes for decades now, yet a range of satellite missions, feature tracking programs, and user approaches have made it a laborious task. To date, there has been no tool developed that would allow a user to obtain displacement maps of any specified glacier simply by establishing the key temporal, spatial and feature tracking parameters. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Glacier velocity measurements enable scientists to map glacier divides and drainage basins (Davies and Glasser, 2012;Pfeffer et al, 2014;Mouginot and Rignot, 2015), track changes in surface melt production and accumulation (Mote, 2007;Sneed and Hamilton, 2007), and address key questions about ice dynamics and the future of glaciers under a changing climate (Stearns et al, 2008;van de Wal et al, 2008;Rignot et al, 2011;Willis et al, 2018;Millan et al, 2019;Altena et al, 2019). Even the earliest glaciologists identified that glaciers may flow as viscous fluids (Forbes, 1840(Forbes, , 1846Bottomley, 1879;Nye, 1952) and later that glacier surface motions reflect a complex interplay between internal deformation, basal sliding, and deformation of subglacial sediments (Deeley and Parr, 1914;Weertman, 1957;Kamb and LaChapelle, 1964;Nye, 1970;Fowler, 2010). Such changes reflect a combination of glacier mass balance and basal conditions -including time-varying hydrology -both of which may respond to climate.…”
Section: Introductionmentioning
confidence: 99%
“…Glacier velocity measurements enable scientists to map glacier divides and drainage basins (Davies and Glasser, 2012;Pfeffer et al, 2014;Mouginot and Rignot, 2015), track changes in surface melt production and accumulation (Mote, 2007;Sneed and Hamilton, 2007), and address key questions about ice dynamics and the future of glaciers under a changing climate (Stearns et al, 2008;van de Wal et al, 2008;Rignot et al, 2011;Willis et al, 2018;Millan et al, 2019;Altena et al, 2019). Even the earliest glaciologists identified that glaciers may flow as viscous fluids (Forbes, 1840(Forbes, , 1846Bottomley, 1879;Nye, 1952) and later that glacier surface motions reflect a complex interplay between internal deformation, basal sliding, and deformation of subglacial sediments (Deeley and Parr, 1914;Weertman, 1957;Kamb and LaChapelle, 1964;Nye, 1970;Fowler, 2010). Such changes reflect a combination of glacier mass balance and basal conditions -including time-varying hydrology -both of which may respond to climate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the geodetic mass balance of the 1980-2010 period was determined to be between −0.7 and −0.8 m of water equivalent per year (Fischer et al, 2015). The SMB stake measurements served to calibrate a mass balance model (Nemec et al, 2009) which was coupled to a higher-order ice flow model to simulate the future evolution of the glacier complex (Zekollari et al, 2014) and to study its response time (Zekollari and Huybrechts, 2015). Furthermore, the ice thickness in the ablation area has previously been measured twice (Zekollari et al, 2013;Langhammer et al, 2019).…”
Section: Study Area and Fieldworkmentioning
confidence: 99%
“…Image registration, also known as image matching and image correlation, geometrically aligns images and allows tracking for accurate 2D change measurements in optical images. It has been used on a local to regional scale to assess motion fields for glaciological [8][9][10], earthquake [11][12][13], dune migration [14,15], rock glacier [16] and landslide studies [5,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%